2009
DOI: 10.1007/s00421-009-1302-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermometry and calorimetry assessment of sweat response during exercise in the heat

Abstract: Our objective was to characterise sweat rate responses in a hot environment during rest and subsequent increasing levels of exercise in relation to thermometrically (i.e., rectal, tympanic, mean skin and mean body temperatures) and calorimetrically derived (i.e., change in body heat storage) thermal parameters. Ten healthy males volunteered and entered an environmental chamber set at 42 degrees C. Participants rested seated during their first hour inside the chamber. Thereafter, they exercised to volitional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…These effects could result in interpretation errors of sEMG findings in human performance studies, depending on the nature of the study and onset of signal deterioration. Furthermore, the rate of sweating changes over time, being dependent on: passive heating (Taniguchi et al, 2011), exercise (Flouris and Cheung, 2010;Smith and Havenith, 2011) and influenced by individual differences in sweat rates (Cotter et al, 1995) as well as time of day (Aoki et al, 2002), seasons (Aoki et al, 2002), gender (Kenny and Jay, 2007;Taniguchi et al, 2011) and age (Dufour and Candas, 2007). This makes sweating a difficult factor to control in experimental studies, especially those carried out in the workplace where the environmental conditions cannot be controlled and protective clothing is often required.…”
Section: Introductionmentioning
confidence: 97%
“…These effects could result in interpretation errors of sEMG findings in human performance studies, depending on the nature of the study and onset of signal deterioration. Furthermore, the rate of sweating changes over time, being dependent on: passive heating (Taniguchi et al, 2011), exercise (Flouris and Cheung, 2010;Smith and Havenith, 2011) and influenced by individual differences in sweat rates (Cotter et al, 1995) as well as time of day (Aoki et al, 2002), seasons (Aoki et al, 2002), gender (Kenny and Jay, 2007;Taniguchi et al, 2011) and age (Dufour and Candas, 2007). This makes sweating a difficult factor to control in experimental studies, especially those carried out in the workplace where the environmental conditions cannot be controlled and protective clothing is often required.…”
Section: Introductionmentioning
confidence: 97%
“…In this paper, we moved one step further by providing a means to estimate Tm using the iDISK technique during rest, exercise, and postexercise recovery in different environments. The Tm data obtained using the novel techniques are valuable for physiologists and biomechanists assessing mechanisms of muscle contraction and the effects of different ergogenic factors, as well as for exercise scientists wanting to maximize athletic performance (13,16,19). Assessing Tm is vital for the achievement of such endeavors, because skeletal muscle function is significantly affected by Tm (36 -38, 41).…”
Section: Discussionmentioning
confidence: 99%
“…These enormous changes in blood flow have a vast effect on the regional distribution of heat and the heat storage patterns, which ultimately affect the entire body’s thermal homeostasis. Therefore, measuring temperature in specific regions of the body, such as the rectum, esophagus, or the visceral organs, can only indicate regional changes in heat content ( Flouris & Cheung, 2010; Flouris & Cheung, 2011; Kenny et al , 2015; Kenny et al , 2017; Taylor et al , 2014; Webb, 1986). Moreover, peripheral tissues can tolerate greater changes in heat with less threat to the health and survivability of the organism, whereas increases in specific organ structures such as the brain can threaten organism health ( Kiyatkin, 2010).…”
Section: Unaccounted Heat In Thermal Physiology Researchmentioning
confidence: 99%
“…For instance, climate models accounting for these recent advances suggest a transition to a positive phase of the Interdecadal Pacific Oscillation, which will increase the warming rate of global surface temperature ( Hawkins et al , 2014; Thoma et al , 2015). Similarly to climate studies, thermal physiology research employing calorimetric methods has shown that temperature measurements at a single region of the body’s core do not (on average) reflect whole-body thermal strain [( Flouris & Cheung, 2010; Kenny et al , 2013; Kenny et al , 2017; Meade et al , 2016; Stapleton et al , 2014; Stapleton et al , 2015; Webb, 1986), including reviews ( Benzinger et al , 1961; Taylor et al , 2014; Webb, 1995)]. In addition to their limited accuracy, such measurements contain a significant time lag, which makes them less effective for scientific purposes and potentially problematic when used in health-related settings.…”
Section: Heat Parallels In the Two Disciplinesmentioning
confidence: 99%